The Challenge of Politics and Sanitation of Khalij e- Fars and its Consequences in Bushehr from the End of Qajar to the Fall of Reza Shah - khadijeh hoseyinzadeh; manizheh Sadri; simin fasihi; manijeh kazemi rashed (تاریخ اسلام)
The prevalence of contagious illnesses, the insufficiency of sanitary facilities as well as the increase of mortality in Iran particularly in Khalij e- Fars region were regarded as the main concerns of the country in the end of Qajar and Pahlavi era. In this very period, the political and economic competitions between the European countries in this region led to the development of new challenges in the domain of politics and sanitation and its consequences were represented in Bushehr city. England with more active role in Khalij e- Fars, took step towards the establishment of quarantine stations in borderline areas including Khalij e- Fars in order to improve the sanitation and fight with the illnesses. The focal point of this writing is the investigation of the challenge between the politics and sanitation in the quarantine of Khalij e- Fars and its consequences in Bushehr from the end of Qajar to the fall of Reza shah by taking advantage of the descriptive- analytical approach, the reports of sanitation, the official documents, the newspapers, in addition to the other sources. The findings of research indicate the competition between European physicians particularly the England ones in Iran related to fighting with diseases led to the improvement of public sanitation in Bushehr. However, the challenge in the domains of politics and sanitation changed the sanitary issue into the political one and consequently, the interference of the European faced with the resistance of people and this challenge was developed by the independency of the quarantine organization of the South